Optimalisasi Potensi Pendidikan Melalui Analisis SWOT dari Perspektif Guru dan Peserta Didik - Rahmawati Rahmawati; Qatrunnada Widhia Nugraha; Rina Agustina; Rini Anjani; Riska Riska; Asep Kadarohman (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This study aims to optimize educational potential through a SWOT analysis from the perspective of teachers and students. This study uses a development research design. The subjects were teachers and students from one of the schools in Bandung City. The results of the SWOT analysis based on teacher responses obtained data that the coordinate position is in quadrant I, namely teachers can utilize strengths to obtain opportunities. Meanwhile, the results of the SWOT based on student responses obtained data that the coordinate position is in quadrant II, namely creating strategies using strengths to overcome threats. Based on this, it was found that the school where the study was conducted has various strengths, such as adequate facilities, good communication between the school and parents, and good academic and non-academic achievements. However, it has weaknesses including suboptimal use of existing facilities and mismatched learning strategies with student needs. In this case, there are opportunities to improve the quality of the school, including scholarship programs, collaboration with research institutions, and increased cooperation with the school environment.